Does family support mediate the effect of anxiety and depression on maternal-fetal attachment in high-risk pregnant women admitted to the maternal-fetal intensive care unit? - Se-Hee Yoon; Mi-Hae Sung (Korean Society of Women Health Nursing, 2021)
Purpose This study investigated the mediating effect of family support in the relationships of anxiety and depression with maternal-fetal attachment among pregnant women admitted to the maternal-fetal intensive care unit (MFICU) in Korea. Methods The participants were high-risk pregnant women with a gestational age of at least 20 weeks who were admitted to MFICUs in Busan and Yangsan. The Korean versions of four measurement tools were used for the self-report questionnaire: Spielberger's State-Trait Anxiety Inventory, the Edinburgh Postnatal Depression Scale, Cobb's family support measurement, and Cranley's maternal-fetal attachment scale. Data were collected from June 22 to September 20, 2020. Out of 124 participants, data from 123 respondents were analyzed. Descriptive statistics and regression analysis were done. Results The average age of participants was 34.1 years. Their anxiety level was moderate (43.57±11.65 points out of 80) and 53.6% were identified as having moderate depression (average 10.13±5.48 points out of 30). Family support was somewhat high (average 43.30±5.03 points out of 55). The average score of maternal-fetal attachment was also somewhat high (73.37±12.14 points out of 96). Family support had a partial mediating effect in the relationships of anxiety and depression with maternal-fetal attachment among high-risk pregnant women admitted to the MFICU. Conclusion Maintaining family support is challenging due to the nature of the MFICU. Considering the mediating effect of family support, establishing an intervention plan to strengthen family support can be helpful as a way to improve maternal-fetal attachment for high-risk pregnant women admitted to the MFICU.